Effects of Fracture Parameters in an Anisotropy Model on P-Wave Azimuthal Amplitude Responses - Fatkhan, Fatkhan (Journal of Engineering and Technological Sciences, 2006)
The study showed that the presence of vertically aligned fractures in reservoir rock could possibly be inferred through analysis of P-wave reflectivity variations with azimuth. The azimuthal amplitude responses measured at an interface separating overburden anisotropy and fractured rock rely on several parameters that can be decomposed into the background rock and the fracture contributions.The effect of fracture porosity on P-wave azimuthal amplitude response is small for moderate incidence angles. For fluid filled fractures P-wave anisotropy is mildly affected. For dry fractures the difference in P-wave anisotropy between low and high fracture porosities is high. This suggests that an assumption of overburden isotropy may result in a large error in predicting the fluid type and saturation.